2019
DOI: 10.3390/ijerph17010136
|View full text |Cite
|
Sign up to set email alerts
|

Spatiotemporal Variations of Particulate and Gaseous Pollutants and Their Relations to Meteorological Parameters: The Case of Xiangyang, China

Abstract: High air pollution levels have become a nationwide problem in China, but limited attention has been paid to prefecture-level cities. Furthermore, different time resolutions between air pollutant level data and meteorological parameters used in many previous studies can lead to biased results. Supported by synchronous measurements of air pollutants and meteorological parameters, including PM2.5, PM10, total suspended particles (TSP), CO, NO2, O3, SO2, temperature, relative humidity, wind speed and direction, at… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
4
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 40 publications
2
4
0
Order By: Relevance
“…In this study, the correlation coefficient between wind speed and AQI was found to be −0.462 ( P < 0.001) through correlation analysis. Some studies also concluded that air pollutants are mainly from anthropogenic emissions, and higher wind speed will carry away pollutants from the city 46,47 . This view supports some of the results of this study that high wind speed has a protective effect on the development of bronchitis, and low wind speed conditions are not conducive to the diffusion and dilution of pollutants, so bronchitis shows a harmful effect under low wind speed conditions.…”
Section: Discussionsupporting
confidence: 87%
See 1 more Smart Citation
“…In this study, the correlation coefficient between wind speed and AQI was found to be −0.462 ( P < 0.001) through correlation analysis. Some studies also concluded that air pollutants are mainly from anthropogenic emissions, and higher wind speed will carry away pollutants from the city 46,47 . This view supports some of the results of this study that high wind speed has a protective effect on the development of bronchitis, and low wind speed conditions are not conducive to the diffusion and dilution of pollutants, so bronchitis shows a harmful effect under low wind speed conditions.…”
Section: Discussionsupporting
confidence: 87%
“…Some studies also concluded that air pollutants are mainly from anthropogenic emissions, and higher wind speed will carry away pollutants from the city. 46,47 This view supports some of the results of this study that high wind speed has a protective effect on the development of bronchitis, and low wind speed conditions are not conducive to the diffusion and dilution of pollutants, so bronchitis shows a harmful effect under low wind speed conditions. Bronchiectasis is usually influenced by abiotic and biotic factors, whereas pneumonia and bronchopneumonia, which are also lower respiratory tract diseases, are more influenced by biotic factors (pathogens).…”
Section: Discussionsupporting
confidence: 77%
“…The particulate matter relationship may be a result of a positive relationship with global radiation at a significant 0.05 level. Global radiation fuels photochemical reactions in the atmosphere, resulting in the formation of particulate matter [26]. The relationship between RH and PM2.5 demonstrates that relative humidity has no effect on fine particle scavenging.…”
Section: Resultsmentioning
confidence: 99%
“…The relationship between RH and PM2.5 demonstrates that relative humidity has no effect on fine particle scavenging. The fact that temperature and O3 have a positive correlation suggests temperature has a positive effect on photochemical reactions [26].…”
Section: Resultsmentioning
confidence: 99%
“…In addition, DEHP is the major PAE that leaches from household wastes [ 44 ] and is also a major component in atmospheric particles [ 45 ]. Recently, PAEs have been found in PM2.5 and PM10 in the ambient air of the Wuhan, Xiangyang, and Xiantao cities [ 46 , 47 , 48 , 49 ]. Moreover, atmospheric transport and deposition are also important sources of organic contaminants in the sediment environment (Mi et al, 2019).…”
Section: Discussionmentioning
confidence: 99%